Social Representations of teachers about COVID-19 (Research, Society and Development, 2022)
Since the end of 2019, the Coronavirus has caused a pandemic state of alert, which has caused the world to adopt protective measures aimed at reducing the spread of the virus. This fact crossed society in all its biopsychosocial dimension, including in the educational scope. Thus, considering the phenomenon of Social Representations, as well as the communication system currently established, the present work aims to identify the signifiers attributed by teachers from Paraíba to COVID-19, given the scenario experienced. This is a quantitative-qualitative, descriptive and exploratory study, which took place in a virtual format with the help of Google Forms between the period from September/2020 to July/2021. The non-probabilistic sample consisted of 450 professors from the state of Paraíba. For data collection, a sociodemographic/labor questionnaire and the Free Association Test (TALP) were used. Data analysis was performed using the SPSS and IRAMUTEQ platforms. Three categories were then developed, which were called: Resilient Mechanisms, verifying how the participants dealt with the entire situation resulting from the pandemic; Prophylaxis, which refers to terms that relate to care and prevention in the face of COVID-19; and Psychosocial Consequences, bringing broader repercussions from the pandemic. Therefore, it was concluded with this research that the vast majority of participants were negatively affected by the pandemic scenario and that the information disseminated via social media ended up influencing the way of view obtained, thus emphasizing the importance of transmitting information with a scientific nature.